Relationship between Cnm‐positive Streptococcus mutans and cerebral microbleeds in humans. (1st September 2015) - Miyatani, F; Kuriyama, N; Watanabe, I; Nomura, R; Nakano, K; Matsui, D; Ozaki, E; Koyama, T; Nishigaki, M; Yamamoto, T; Mizuno, T; Tamura, A; et al.
<x xml:space="preserve">Abstract</x> Objective Cerebral hemorrhage has been shown to occur in animals experimentally infected with Streptococcus mutans carrying the collagen‐binding Cnm gene. However, the relationship between cerebral microbleeds and oral hygiene, with a focus on Cnm gene‐positive S. mutans infection, remains unclear. Material and Methods One hundred and thirty‐nine subjects participated. The presence or absence of Cnm‐positive S. mutans and its collagen‐binding activity were investigated using saliva samples, and relationship with cerebral microbleeds detected on MRI investigated, including clinical information and oral parameters. Results Fifty‐one subjects were identified as Cnm‐positive S. mutans carriers (36.7%), with cerebral microbleeds being detected in 43 (30.9%). A significantly larger number of subjects carried Cnm‐positive S. mutans in the cerebral microbleeds (+) group. S. mutans with Cnm collagen‐binding ability was detected in 39 (28.1%) of all subjects, and the adjusted odds ratio for cerebral microbleeds in the Cnm‐positive group was 14.4. Regarding the presence of cerebral microbleeds, no significant differences were noted in the number of remaining teeth, dental caries, or in classic arteriosclerosis risk factors. Conclusions The occurrence of cerebral microbleeds was higher in subjects carrying Cnm‐positive S. mutans, indicating that the presence of Cnm‐positive S. mutans increases cerebral microbleeds, and is an independent risk for the development of cerebrovascular disorders.